Machinery Breakdown: a Chaos-Based Explanation - Montenegro Joo, Javier (2009)
An attempt to explain the process of machinery breakdown by means of Chaos Theory is presented. Machines carry out repetitive tasks that may be mathematically modelled as combinations of forced oscillatory motions; consequently these are perfect candidates to eventually evolve towards chaos. The exposition is made having as a model the route to chaos in the damped and forced non-linear oscillator.